A7.11 Genetic Variation in Promoter Sequence of B-Cell-Activating Factor of the TNF Family (BAFF) in Patients with Idiopathic Inflammatory Myopathies (IIM). (25th February 2013) - Faustova, M; Plestilova, L; Hulejova, H; Pecha, O; Betteridge, Z; Mann, H; Putova, I; Vencovsky, J; Novota, P; Krystufkova, O
Abstract : Background and Objectives: B-cell activating factor of the TNF family (BAFF) is important for B cell maturation and plays a role in (auto)antibodies production. Elevated serum levels in relation to autoantibodies were documented in patients with IIM. Promoter region of BAFF gene contains several known sites with single nucleotide polymorphism (SNPs). An association between Rs9514828 (–871 C/T) SNP and susceptibility to idiopathic trombocytopaenic purpura was shown and possible relations to systemic lupus erythematosus, rheumatoid arthritis or Sjögren's syndrome were suggested but in IIM have not been studied yet. Here, we analysed relation of four BAFF SNPs located in the BAFF gene promoter with the development of IIM. Materials and Methods: 146 patients with polymyositis (PM), 150 with dermatomyositis (DM), 11 patients with juvenile DM and 4 patients with inclusion body myositis and 103 healthy individuals were included. Four SNPs located upstream in the BAFF gene (Rs9514827 (–2841 T/C); Rs3759467 (–2704 T/C); Rs1041569 (–2701 T/A); Rs9514828 (–871 C/T)) were analysed by direct DNA sequencing. Serum levels of BAFF (s-BAFF) were evaluated using ELISA. Autoantibodies were detected with immunoprecipitation. The chi square test for analysis of alleles and genotypes associations and SNPStats software for haplotype frequency studies were used. Results: Significantly higher frequency of –2701T allele was present in patients (18%) compared to healthy controls (12%) (P = 0.029; OR 1.684 (CI 95% = 1.050 – 2.699)). Additionally, increased –2841T allele (P = 0.086), –2841TT, CT genotype (P = 0.066) and –2701TT, AT genotype (P = 0.079) frequencies were observed in patients. SNPs were in strong linkage disequilibrium and formed four common haplotypes (TTAC, CTAT, TCAC, TTTT), with significantly different frequency (>9%) distributions between patients and controls (global P-value < 0.038). Higher frequency of TTTT haplotype was present in patients (16.2%) compared to controls (9.3%; OR 1.99 (95% CI 1.15–3.47; P < 0.015)) relative to the most frequent haplotype TTAC. Significantly higher s-BAFF levels were detected in patients compared to healthy controls (P < 0.0001) and in patients with anti-Jo-1 or anti-PMScl autoantibodies compared to patients without autoantibodies (P = 0.028, P < 0.037 respectively). Higher s-BAFF levels with –2704T allele within anti-Jo-1+ patients (P < 0.043) were found. Conclusions: We describe significant association of SNP (Rs1041569) with myositis and a relation of SNP (Rs3759467) to presence of anti-Jo-1 autoantibodies and s-BAFF levels. These results should be confirmed in an independent cohort of patients and possible relations of s-BAFF levels with disease activity and treatment should be considered. Acknowledgement: IGA -Ministry of Health of the Czech Republic NT/12438–4.